Cropping practices and labor requirements in field operations for major crops in Ghana: What needs to be mechanized? - Ngeleza, Guyslain K.; Owusua, Rebecca; Jimah, Kipo; Kolavalli, Shashidhara (International Food Policy Research Institute, 2011)
This study is to examine the labor requirements associated with different cropping systems in Ghana in order to guide the prioritization of investments in mechanization in the country. First, major cropping systems are identified in the country by adopting the cropping pattern approach of Ruthenberg (1983), who defined farming systems according to the leading crop activities. Second, labor requirements and costs of production of crops in the various systems are examined at various levels of substitution of either herbicides or animal and mechanical traction for labor. We found that the total labor requirements varied among cropping systems. The requirements were particularly high in the two cocoa cropping systems in the forest zones. The requirements were particularly high for land preparation and crop maintenance. Looking across crops, land preparation and crop maintenance took the largest share of labor for cassava, yam, and maize. Rice, on the other hand, required large shares of labor for land preparation and harvesting. When all the systems are considered together, however, crop maintenance required more labor than land preparation. In response to apparent unavailability and cost of labor, farmers are increasingly demanding mechanical traction for land preparation in Ghana. The benefits of mechanizing land preparation depend on both the system and the type of crop cultivated. Mechanization of land preparation for cassava in the vegetable belt, for instance, is more labor saving and cost effective than m Mechanization of land preparation for cassava in cereals belt. Within systems, there is also variation across crops. Where mechanization is not feasible for land preparation or not yet adopted for other field operations such as weeding, an alternative and common substitution for labor in crop production is herbicides. Herbicides are used to clear land for planting as well as to control weeds in standing crops. We found that where herbicide was used, its application reduced labor requirements for land preparation significantly. Selective herbicides were used to control weeds in all the crops examined and in all the belts except the vegetable belt. They also reduced labor use for weeding drastically.